Pengaruh Bantuan Sarana Produksi Pertanian Terhadap Pendapatan Petani Padi di Kecamatan Indrapuri Kabupaten Aceh Besar - Asmi Hidayah Putri; Ahmad Humam Hamid; Teuku Makmur (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
This study aims to determine whether there is an effect of agricultural production facilities assistance on the income of rice farmers, and to determine the difference in the income of rice farmers who receive agricultural production facilities assistance with rice farmers who do not receive agricultural production facilities assistance. Determination of the sample in this study was carried out using simple random sampling and took 10% of the total sample obtained, while the samples obtained were 43 farmers who received assistance for agricultural production facilities and 43 samples who did not receive assistance for agricultural production facilities. The analytical technique used in this research is the analysis of multiple regression test and t test (Independent sample T Test). Based on the results of the multiple regression test, it shows that overall the rice seed assistance variable, and the fertilizer assistance variable, have a significant effect on the income variable with a significance value of 0.03 0.05 while partially only the fertilizer assistance variable has a significant effect on the income variable with a significance value of 0.045 0.05, with tcount (2.487 2.021), while for the seed assistance variable with a significance value of 0.012 0.05, the obtained tcount (0.828 2.502) which means that there is no partial effect between the seed variable and income. Then the difference in the average net income of rice farmers who received assistance for agricultural production facilities and those who did not receive assistance for agricultural production facilities was Rp. 3,950,738.